Changes in Haemodynamic Variables during total Abdominal Hystrectomy: Comparison of General and Spinal Anesthesia - Hina Zubair, Muhammad Nadeem Khan, Aurooj Fatima, Aisha Yousaf, Shahid Adalat Chaudry, Saima Perveen, Akkad Rafiq, Asad Ali Chaudhry (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Surgical patients may be exposed to stress response that may be presented with hypertension, tachycardia, arrhythmia and myocardial ischemia. Stress response may expose the patients for serious outcome, especially patients with cardiovascular disease. Objective: To evaluate the effect of general anesthesia and spinal anesthesia on the perioperative hemodynamic stability in patients undergoing total abdominal hysterectomy. Study Design: Prospective, randomized clinical trial Place and Duration of Study: Department of Anesthesia, Divisional Headquarters Teaching Hospital Mirpur AJK from 1st January 2022 to 30th June 2023. Methodology: Two hundred patients scheduled for elective total abdominal hysterectomy classified randomly into two groups; general anesthesia (GA) and spinal anesthesia (SA) and they were equally divided 100 in each group. The primary outcome was hemodynamic stability as assessed by changes in the heart rate, blood pressure, electrocardiography changes and SPO2 (pulse oximetry). Results: The GA group showed significant increases in heart rate and systolic blood pressure, with heart rate rising from 80 bpm at baseline (T0) to 98 bpm at 15 minutes (T1), peaking at 102 bpm at 30 minutes (T2), and gradually decreasing to 90 bpm by the end of surgery (T5). Systolic blood pressure increased from 120 mmHg at baseline to 145 mmHg at 30 minutes (T2) and remained elevated at 130 mmHg by the end of surgery (T5). In contrast the SA group experienced minimal fluctuations, with heart rate remaining stable around 82 bpm at baseline, reaching only 85 bpm by the end of surgery. Conclusions: General anesthesia causes minimal changes in hemodynamic variables compared to spinal anesthesia in patients undergoing total abdominal hysterectomy. Keywords: Spinal anesthesia, General anesthesia, Tachycardia, Hypertension, Hypotension.